Orthotopic transplantation of the bioengineered lung using a mouse-scale perfusion-based bioreactor and human primary endothelial cells - Fumiko Tomiyama; Takaya Suzuki; Tatsuaki Watanabe; Jun Miyanaga; Anna Suzuki; Takayasu Ito; Sho Murai; Yuyo Suzuki; Hiromichi Niikawa; Hisashi Oishi; Hirotsugu Notsuda; Yui Watanabe; et al. (Scientific Reports, 2024)
Abstract Whole lung engineering and the transplantation of its products is an ambitious goal and ultimately a viable solution for alleviating the donor-shortage crisis for lung transplants. There are several limitations currently impeding progress in the field with a major obstacle being efficient revascularization of decellularized scaffolds, which requires an extremely large number of cells when using larger pre-clinical animal models. Here, we developed a simple but effective experimental pulmonary bioengineering platform by utilizing the lung as a scaffold. Revascularization of pulmonary vasculature using human umbilical cord vein endothelial cells was feasible using a novel in-house developed perfusion-based bioreactor. The endothelial lumens formed in the peripheral alveolar area were confirmed using a transmission electron microscope. The quality of engineered lung vasculature was evaluated using box-counting analysis of histological images. The engineered mouse lungs were successfully transplanted into the orthotopic thoracic cavity. The engineered vasculature in the lung scaffold showed blood perfusion after transplantation without significant hemorrhage. The mouse-based lung bioengineering system can be utilized as an efficient ex-vivo screening platform for lung tissue engineering.